The Role of Femtech (Female Technology) in Strengthening Women’s Representation in the Digital Technology Sector - Damayanti, Alfina; Sundari, Anisa (Journal of Feminism and Gender Studies, 2026)
The global technology sector has confronted challenges related to the gender gap, with low representation of women in leadership positions, entrepreneurship, and technology development. This journal article examines how the emergence and growth of Femtech (female technology) catalyze the strengthening of women's representation in the digital technology industry. Femtech is a new term that has rapidly developed as an innovative sector focusing on technological solutions for women's health and wellness imperatives. Through qualitative analysis by collecting data on the impact of Femtech companies in the technology industry, this research explores the role of Femtech in strengthening women's position in the digital technology sector. Femtech has engendered inclusive pathways facilitating women's integration and advancement within the technology sector, with women comprising 80% of Femtech founders in 2022. This research examines the role of Femtech in strengthening women’s representation in the digital technology sector as an entry point that reduces barriers to entry for women in the technology sector. The strategic position of women in the technology industrial sector will enhance their role as decision-maker. Furthermore, Femtech serves as a transformative catalyst that facilitates system reforms to gender biases prevalent in the digital technology sector.